A study of customer satisfaction towrads service quality in Hospital Islam Az Zahrah / Ahmad Omar Abdullah Zaik - Abdullah Zaik, Ahmad Omar (2017)
The growth of the economy, technology and knowledge are the things that push all the company come out with a best offering to the customer and try to be different from others. Set up the business is much simpler than maintaining its survival in the industry. In the healthcare industry people are compete to offer a better service that others, the company may offer a unique service or a best quality of services in satisfying the customer. Hospital Islam Az Zahrah are losing their focus on quality of services, they try to come out with many services without maintaining its quality. For this reason, other than to study the customer satisfaction towards service quality in Hospital Islam Az Zahrah, this thesis also help the company to see their customer level of satisfaction towards hospital services. In order to achieve this, both of primary and secondary sources are used. The questionnaire were distributed to sixty respondent in gaining data process. All the sixty respondents are patient who receive a treatment in warded during a distribution time. The result of this research point out that from the five service quality dimension only two of them are significant with customer satisfaction which are responsiveness and tangibles. Assurance variable were the highest score in mean which means majority people are agree with the statement. From the result of study, researcher are able to understand the level of service quality in Hospital Islam Az Zahrah and answer all the research question.